2014
DOI: 10.1002/0471142727.mb0718s108
|View full text |Cite
|
Sign up to set email alerts
|

Next‐Gen Sequencing‐Based Mapping and Identification of Ethyl Methanesulfonate‐Induced Mutations in Arabidopsis thaliana

Abstract: Forward genetic analysis using ethyl methanesulfonate (EMS) mutagenesis has proven to be a powerful tool in biological research, but identification and cloning of causal mutations by conventional genetic mapping approaches is a painstaking process. Recent advances in next-gen sequencing have greatly invigorated the process of identifying EMS-induced mutations corresponding to a specific phenotype in model genetic hosts, including the plant Arabidopsis thaliana and the nematode Caenorhabditis elegans. Next-gen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…We used a genome resequencing-assisted approach 22,23 to map and identify the HSM1 gene. Computational analyses described in Methods showed that the SGT1b gene (At4g11260) was the most likely candidate corresponding to hsm1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a genome resequencing-assisted approach 22,23 to map and identify the HSM1 gene. Computational analyses described in Methods showed that the SGT1b gene (At4g11260) was the most likely candidate corresponding to hsm1 .…”
Section: Resultsmentioning
confidence: 99%
“…The HSM1 ( SGT1b ) gene was cloned following a genome resequencing–assisted mapping and cloning procedure for EMS mutants 22,23 . Briefly, hsm1 was outcrossed to Ler to yield an F1 hybrid, followed by self-fertilization to produce F2 segregants.…”
Section: Methodsmentioning
confidence: 99%
“…The homozygous pho2 mutant (HNE8536) was prepared as described by Wang et al (2009). Hydroponic and soil pot experiments were performed as described by Zhou et al (2008).…”
Section: Methodsmentioning
confidence: 99%
“…An inorganic Pi content measurement was performed following the method described by Zhou et al (2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation